'All the helth and life of the sacraments... I it am': Julian of Norwich and the sacrament of penance - Pennington, E (2014)
This thesis explores a long-neglected area of Julian’s work, namely her devotional and pastoral understanding of the nature of sin and the sacrament of penance. Her two texts reveal a deep concern, set within the context of a rise in lay penitential piety, for those devout who continued to experience a sense of shame and dread of sin, even after confession to a priest. By means of a close comparative reading of Julian's short and long texts of A Revelation of Divine Love, and an examination of a wide range of Middle English devotional texts and manuals, as well as a breadth of Julian scholarship to date, I argue that Julian addresses the devotional and ecclesiastical concerns of late fourteenth-century England in the problem of sin and confession for the ordinary believer. By articulating her revelation in the penitential terms of the manuals of the Church, Julian reveals the extent to which the daily devotional life of 'holy moder church' is the means by which the saving love of Christ is realised and made accessible to the penitent. Within her writing Julian seeks to reassure her reader that God has dealt with sin and triumphed over the devil but in order to do this she must alter their understanding of a contrition-centred sacrament. For this reason Julian sets up a crisis of understanding within her long text between the 'common teaching of holy church' and her revelation of love. This conflict is deliberately left unresolved in order that, in scholastic terms, two opposing arguments in opposition may jointly illuminate the necessity of sin and penance in bringing the soul to the proper state of humility and the mercy and grace of the loving Lord in forgiveness. In so doing it is argued that, within Julian’s writing, the pastoral process of penance is integral to those who desire a more intimate relationship with God. The thesis consists of four chapters which first, locates Julian's short and long versions of A Revelation of Divine Love within the climate of the late-fourteenth century; secondly, it charts the rise of the significance of the role of the penitent within the history of penance which led to an increasing lack of confidence within the late fourteenth century in the ability of the confessional encounter to alleviate the sense of sin experienced by some devout souls; thirdly, I analyse the extent to which Julian's short and long version of a Revelation of Divine Love reflect and address this catechetical and penitential climate in her theology of sin and penance; and finally the thesis poses the question of the extent to which Julian's work can be considered as a penitential text which seeks to bring ease and comfort of the assurance of sins forgiven through the everyday practices of the Church. It is concluded that Julian's writing reveals a fascinating and significant contribution to late fourteenth-century thought on penance and brings a fresh reading of Julian's texts.